The house as a story organizer and a shelter from reality in the Colombian novel of the twenty-first Century: the cases of Fernando Vallejo and Santiago Gamboa - Andrés Fernando Forero Gómez; Dewi Mayanthi Utami Heru (Estudios de Teoría Literaria, 2024)
This text studies the role of the house as a key space to understand the contemporary individual in two Colombian novels of the second decade of the twenty-first century: Casablanca la bella (2013)by Fernando Vallejo and Una casa en Bogotá (2014) by Santiago Gamboa. First, a historical revision of the role of this space in Latin American literature is presented. Later on, through the concept of “Autofiction” and the perspective that Gaston Bachelard and other authors offer regarding the link between houses and inner life, the article characterizes the use that Gamboa and Vallejo give to the house as a resource that organizes the plot and defines the narrator-protagonist through the analogy between it and the spaces he inhabits. Finally, the article analyzes how in these two works of literature the house is reconfigured as a location that promotes nostalgia and functions as an illusory shelter from outside reality. Thus, these two novels provide a new role for the house within the evolution of Latin American literature, since they integrate the inner world of the individual with the social reality of its country through the use of the space of home.